Analysis of the Readiness of Vocational School Teachers for the Expertise Program Electrical Engineering in Developing Learning Based on Local Potential - Supraptono, Eko; Sonhaji, Sonhaji; Kurniawan, Galang Wahid; Sunardiyo, Said; Irfan, Mohamad; Hidayattullah, Ardhana Luthfi (Universitas Negeri Semarang, 2025)
This study aims to analyze the readiness of teachers of the Electrical Engineering Expertise Program at SMK Negeri Semarang City in developing learning based on local potential in the digital era. Teacher readiness is reviewed through aspects of pedagogic, professional, digital, teaching experience, and training or certification. Local potential-based learning is understood as integrating regional resources and local wisdom into the curriculum through contextual methods with the support of digital technology. The research method uses a mixed approach. Quantitative data is obtained through questionnaires to measure teachers' readiness levels, while qualitative data is collected through interviews, classroom observations, and analysis of curriculum documents. Quantitative data analysis was carried out with descriptive statistics and linear regression to identify relationships between variables, while qualitative data were analyzed thematically to strengthen quantitative findings. The study's results are expected to reveal the supporting and inhibiting factors in implementing local potential-based learning, such as the limitations of digital infrastructure, the lack of relevant training, and education policies that are not optimal to encourage technology integration. Theoretically, this research contributes to enriching the study of teacher readiness by placing local potential as the basis for vocational learning innovation. Practically, the research results are expected to be a reference for education stakeholders to design strategies for increasing teacher capacity and policies more adaptive to technological developments and local industrial needs.